Do salinity, limb autotomy and crab sources stimulate shedding efficiency of mud crab in soft-shell production? - Sakib, Md. Hashmi; Ahmmed, Shawon; Mondal, Debashis Kumar; Islam, Md. Latiful; Mahmud, Yahia (Universiti Kebangsaan Malaysia, 2023)
The present study was conducted to optimize the water salinity, limb autotomy and growth performance of Juvenile mud crabs (JMC) (Scylla olivacea) cultured in control habitat (tanks, hatchery) compared to wild sources. In this regard, a study was performed in tanks with 5, 10, 15 ppt salinity level and in a pond having natural salinity level (control). After seven weeks of JMC culturing, it was observed that better growth attributes including survival rate, weight gain and shorter shedding period of JMC was attained at 15 ppt salinity in tanks compared to control. This optimized salinity level (15 ppt) was considerd for the second study where JMC legs were autotomized. In this study, better growth performance attributes were observed when both side walking legs were autotomized compared to one side walking legs autotomy and no autotomy. Considering the same salinity level (15 ppt), the third study was conducted to evaluate the growth performance of JMC cultured in hatchery (pilot scale) with their wild counterperts. Result showed that higher moulting rate and better growth performance (faster weight gain) of JMC were achieved in hatchery compared to wild cultured. However, JMC collected from hatchery and wild habitat acquired the same carapace width (CW) and body weight (BW) after twenty days rearing.